2015
DOI: 10.1016/j.virol.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

STAT2-dependent induction of RNA adenosine deaminase ADAR1 by type I interferon differs between mouse and human cells in the requirement for STAT1

Abstract: Expression of adenosine deaminase acting on RNA1 (ADAR1) is driven by alternative promoters. Promoter PA, activated by interferon (IFN), produces transcripts that encode the inducible p150 ADAR1 protein, whereas PB specifies the constitutively expressed p110 protein. We show using Stat1−/−, Stat2−/− and IRF9−/− MEFs that induction of ADAR1 p150 occurs by STAT2- and IRF9-dependent signaling that is enhanced by, but not obligatorily dependent upon, STAT1. Chromatin immunoprecipitation analysis demonstrated STAT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…In present study, we observed ADAR1 expression was induced after H 2 O 2 treatment in NCM. Previous reports revealed a STAT-2 dependent process of transcriptional activation of IFN-induced ADAR1 expression in mouse embryo fibroblast cells38. In our study, we confirmed H 2 O 2 induced ADAR1 expression in NCM was also STAT-2 dependent.…”
Section: Discussionsupporting
confidence: 89%
“…In present study, we observed ADAR1 expression was induced after H 2 O 2 treatment in NCM. Previous reports revealed a STAT-2 dependent process of transcriptional activation of IFN-induced ADAR1 expression in mouse embryo fibroblast cells38. In our study, we confirmed H 2 O 2 induced ADAR1 expression in NCM was also STAT-2 dependent.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies suggest that ADAR1 expression is enhanced by inflammatory cytokine signaling that activates STAT binding to the ADAR1 promoter (George et al, 2008; George and Samuel, 2015). Thus, cytokine receptor and downstream target gene expression were analyzed by RNA-seq of fluorescence-activated cell sorting (FACS)-purified normal, CP, and BC progenitors (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Transcripts of inflammatory cytokine-associated receptor genes, which signal through the JAK-STAT pathway, and their downstream target genes were increased in BC compared with normal and CP progenitors (Figures 1A and S1A–E). Compared with CP, BC progenitors harbored increased levels of IFNγR1 and IL-3Rα, which can signal through JAK2 and activate ADAR1 transcription by binding of STATs to the ADAR1 promoter (Figure 1B) (George and Samuel, 2015). In addition, BC CML harbored increased expression of JAK/STAT signaling pathway genes and JAK2 transcripts compared with normal progenitors (Figures 1C and S1F).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, neither Stat1 Ϫ/Ϫ nor Stat2 Ϫ/Ϫ MEFs showed IFN-induced editing. ADAR1 is induced by IFN through JAK-STAT signaling, both in mouse MEFs and human 2fTGH cells (36,38). Likewise, PKR is induced by IFN through JAK-STAT signaling (14,15).…”
Section: Discussionmentioning
confidence: 99%